Diagnostic accuracy of cone beam computed tomography in identification and postoperative evaluation of furcation defects - Natasha Pajnigara; Abhay Kolte; Rajashri Kolte; Nilufer Pajnigara; Vrushali Lathiya (Wolters Kluwer Medknow Publications, 2016)
Background: Decision-making in periodontal therapeutics is critical and is influenced by accurate diagnosis of osseous defects, especially furcation involvement. Commonly used diagnostic methods such as clinical probing and conventional radiography have their own limitations. Hence, this study was planned to evaluate the dimensions of furcation defects clinically (pre- and post-surgery), intra-surgically, and by cone beam computed tomography (CBCT) (pre- and post-surgery). Materials and Methods: The study comprised a total of 200 Grade II furcation defects in forty patients, with a mean age of 38.05 ± 4.77 years diagnosed with chronic periodontitis which were evaluated clinically (pre- and post-surgically), by CBCT (pre- and post-surgically), and intrasurgically after flap reflection (40 defects in each). After the presurgical clinical and CBCT measurements, demineralized freeze-dried bone allograft was placed in the furcation defect and the flaps were sutured back. Six months later, these defects were evaluated by recording measurements clinically, i.e., postsurgery clinical measurements and also postsurgery CBCT measurements (40 defects each). Results: Presurgery clinical measurements (vertical 6.15 ± 1.71 mm and horizontal 3.05 ± 0.84 mm) and CBCT measurements (vertical 7.69 ± 1.67 mm and horizontal 4.62 ± 0.77 mm) underestimated intrasurgery measurements (vertical 8.025 ± 1.67 mm and horizontal 4.82 ± 0.67 mm) in both vertical and horizontal aspects, and the difference was statistically not significant (vertical P = 1.000, 95% confidence interval [CI], horizontal P = 0.867, 95% CI). Further, postsurgery clinical measurements (vertical 2.9 ± 0.74 mm and horizontal 1.52 ± 0.59 mm) underestimated CBCT measurements (vertical 3.67 ± 1.17 mm and horizontal 2.45 ± 0.48 mm). There was statistically significant difference between presurgery clinical-presurgery CBCT (P < 0.0001, 95% CI) versus postsurgery clinical-postsurgery CBCT (P < 0.0001, 95% CI) values in both vertical and horizontal aspects. Conclusion: The use of CBCT appears to be prudent for accurate diagnosis of furcation defects in advanced periodontal diseases. Presurgical and postsurgical three-dimensional imaging enable the clinician to optimize treatment decisions and assess the quantum of healing more definitively.